Influence of inter-aquifer leakage on well-injection capacity: Theory and aquifer-scale mapping for artificial recharge - SHANDILYA RAGHWENDRA NARAYAN; Bresciani, Etienne; Runkel, Anthony C.; Higgins, Rebecca; Lee, Seunghak; Kang, Peter K. (Academic Press, 2022)
Aquifer storage and recovery (ASR) is an important water resources management technique that involves the injection of a large volume of water underground. For the successful implementation of an ASR project, a target aquifer should have a sufficient injection capacity, which is the maximum volume of water that can be safely injected. In nature, no aquitard is perfectly impermeable, and inter-aquifer leakage may have a major impact on injection capacity. Despite the importance of determining the injection capacity for ASR planning, there is no quantitative methodology that estimates the injection capacity of leaky aquifers. In this study, we first develop a solution for injection capacity with inter-aquifer leakage based on the Hantush - Jacob solution, and conduct a comprehensive sensitivity analysis to elucidate the influence of inter-aquifer leakage on injection capacity. From the sensitivity analysis, we show that inter-aquifer leakage can impact injection capacity by more than one order of magnitude, depending on the hydrogeological and operational parameters. We then develop a practical mapping methodology that estimates the injection capacity of leaky aquifers. We demonstrate the proposed methodology by applying it to a potential ASR site in Minnesota, USA, where ASR is considered as a solution to alleviate groundwater contamination by PFAS chemicals. The case study results reveal significant spatial variability in injection capacity over the study area and show an average increase in the injection capacity of about 26% compared to that in the nonleaky scenario. We also analyze the uncertainty in the estimated injection capacity due to the variability of aquitard properties and show that the variability of aquitard vertical hydraulic conductivity leads to a larger uncertainty in the estimated injection capacity than does the variability of aquitard thickness. This study elucidates the effects of inter-aquifer leakage on injection capacity and provides a practical methodology for injection capacity mapping.